AXL/MET dual inhibitor, CB469, has activity in non-small cell lung cancer with acquired resistance to EGFR TKI with AXL or MET activation. (August 2020) - Yang, Yu-Mi; Jang, Yoon; Lee, Sang Hyuk; Kang, Beodeul; Lim, Sun Min
Highlights: Resistant cells showed activation and phosphorylation of AXL and MET. CB469 and EGFR TKIs inhibited cell proliferation and colony formation rates. The combination of CB469 and erlotinib induced apoptosis of resistant cells. Resistant cells showed an interaction of AXL and MET . CB469 and EGFR TKIs showed antitumor activity in xenograft models. Abstract: Objectives: In non–small cell lung cancer (NSCLC) with epidermal growth factor receptor ( EGFR ) mutations, acquired resistance to EGFR-tyrosine kinase inhibitors (EGFR-TKIs) may occur via bypass signals such as AXL or MET activation. We investigated the antitumor activity of CB469, a newly developed drug that targets both AXL and MET, in EGFR TKI-resistant NSCLC cells. Materials and methods: We generated EGFR TKI-resistant NSCLC cell lines with acquired resistance to erlotinib, gefitinib, and osimertinib (PC9/ER, HCC827/GR and HCC827/OR, respectively). We characterized the mechanisms of CB469 action in resistant cells and investigated the antitumor efficacy of CB469 both in vitro and in vivo . Results: Resistant cells showed activation of phosphorylated EGFR, as well as AXL and MET activation and phosphorylation. The combination of CB469 and EGFR TKIs synergistically inhibited cell proliferation and colony formation rates in resistant cell lines. The combination of CB469 and erlotinib induced apoptosis of PC9/ER cells. Mechanistically, resistant cells showed an interaction of AXL and MET . CB469 and EGFR TKI also demonstrated antitumor activity by reducing phosphorylated AXL and MET in mouse xenograft models with HCC827/GR cells. Conclusion: The combination of CB469 and EGFR TKI can overcome the acquired resistance to EGFR TKI mediated by AXL and MET activation. We anticipate that the dual inhibitory actions of CB469 will assist with the development of targeted therapy for EGFR -mutant NSCLC patients who fail initial EGFR TKI therapy.